Exploring the influence of eWOM in buying behavior - F. Javier Rondan Catalu\~na; Jorge Arenas Gaitán; Patricio Ramirez Correa (The International Journal of Management Science and Information Technology (IJMSIT), 2014)
There is lack of published studies about the relationship between eWOM from SNS or Internet and purchase. This study intends to make a contribution to the understanding of this phenomenon. In order to do this, the research separates the eWOM arisen from the Internet and the eWOM arisen from SNS, and it includes gender as a moderator variable. Furthermore, the inclusion of experience and search goods in the analysis enriches the implications provided. In short, the main proposal of this study is to analyze the influence of eWOM and Internet referrals across different product types, including gender as a moderator variable.
Keywords: 650; eWOM; SNS; buying behavior; Internet